2017
DOI: 10.1590/0104-6632.20170343s2015070
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous photo-Fenton and photocatalytic degradation studies of 2-chloro-4-nitrophenol (2Cl4NP) using foundry sand and TiO2 coated cement/clay beads

Abstract: -Cement and clay beads coated with TiO 2 were used for the photo-degradation and mineralization of 2-chloro-4-nitrophenol (2Cl4NP) along with a heterogeneous solar photo-Fenton process using foundry sand (FS) as the iron source. The degradation process was optimized using slurry photocatalysis where 96% degradation of 2Cl4NP was achieved in 120 min at optimized conditions of C0=50 mgL -1 , pH=4, 0.75 gL -1 TiO 2 and H 2 O 2 = 0.1 mL/200 mL. Degradation of 2Cl4NP was analyzed through HPLC along with UV-Visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The results show the high stability of the Fe–TiO 2 -allophane catalysts and confirm that with these catalysts, the dual-effect process occurs in a heterogeneous phase. This is the opposite of the dual effect process proposed in the literature, where the process is favored by the soluble iron species from catalyst leaching [ 17 , 18 , 20 , 71 ].
Fig.
…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The results show the high stability of the Fe–TiO 2 -allophane catalysts and confirm that with these catalysts, the dual-effect process occurs in a heterogeneous phase. This is the opposite of the dual effect process proposed in the literature, where the process is favored by the soluble iron species from catalyst leaching [ 17 , 18 , 20 , 71 ].
Fig.
…”
Section: Resultsmentioning
confidence: 76%
“…The Bansal research group [ [17] , [18] , [19] ] first proposed the AOP process called the "dual-effect," which combines the advantages of the photo Fenton and photocatalysis processes. In this process, a synergetic effect has been reported by enhancing the degradation efficiency and reducing the time of photocatalytic reactions compared with both processes separately [ [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…8 FS has also been used for environmental remediation purposes. For example, Aggarwal et al 9 demonstrated that it is possible to degrade 2-chloro-4-nitrophenol by the photo-Fenton process, in a batch reactor, using foundry sand as the iron source, which was achieved in 105 min under solar light irradiation and 0.025% in volume of H 2 O 2 . Despite all these examples, no studies regarding electrochemical applications were found for this material, making this report probably the first to tap into the electrocatalytic properties of this specific waste onto HER.…”
mentioning
confidence: 99%